Image-based Detection of Coconut Scale (aspiodotus rigidus) Infestation using Image Data Preprocessing and Augmentation Techniques and Convolutional Neural Networks - Maderazo, Andrea Marie (University of the Philippines, 2023)
ABSTRACT